Serum Adipocytokine Levels in Prostate Cancer Patients - Arısan, Serdar; Atış, Gökhan; Palavan Ünsal, Narçin; Ergenekon, Erbil; ARISAN, ELİF DAMLA (Karger, Allschwilerstrasse 10, Ch-4009 Basel, Switzerland, 2009)
Introduction: We estimated the circulating levels of adipocytokines such as adiponectin and leptin in nonobese nondiabetic prostate cancer (PCa) patients and compared the results with controls and benign prostate hyperplasia (BPH) patients. Material and Methods: Fifty patients with PCa, 20 patients with BPH and 50 healthy volunteers were entered into the study. Their blood samples were investigated for adipocytokines with the ELISA method. Results: Adiponectin levels were determined as 8.9 and 5.5 mu g/ml for the same patients. Leptin concentration was 14.78 ng/ml in organ-confined PCa patients, and 15.24 ng/ml in advanced PCa patients. In control patients, adiponectin and leptin levels were 18.4 and 12.98 ng/ml, respectively. Conclusion: Serum adipocytokine levels of PCa patients were significantly different from those of controls and BPH patients who were not obese or diabetic. Therefore, further molecular investigation of these adipocytokines will help understand the mechanism. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Prostate cancer; Insulin; Adiponectin; radical prostatectomy; leptin; obesity; adiponectin; risk; adipokines; insulin; weight; breast; Prostat kanseri; şişmanlık; İnsülin; radikal prostatektomi; ağırlık